Kedudukan Ketetapan Majelis Permusyawaratan Rakyat dalam Tata Hukum Indonesia Berdasarkan Undang-Undang Dasar 1945 - Ammar Abdulah Arfan (Universitas Bandar Lampung (UBL), 2011)
This study is about of the MajelisPermusyawaratan Rakyat decision under the legalprocedures of 1945 Constitution. The presence of MPR after the Amendment of 1945Constitution is still causing problems, because there are three MPR is declared valid.In fact, MPR had no longer a source of formal law since the enactment of Law No.10of 2004 on the establishment of legislation. It happened because most of the substanceof the MPR is not deposited in the legislation and just to avoid a legal vacuum. Forexample some of the problems caused by the separation of East Timor from Indonesia.To that end, the MPR was declared no longer valid should be viewed as a formalsource of law but as a legal source material. However, with the enactment Law No.12year 2011 on the establishment of legislation, the MPR Decisions have another runway.Article 10 Law No.12 year 2011 stipulates that MPR is one of the hierarcy of legalnorms in Indonesia.